Analisis Anggaran Pendapatan dan Belanja Daerah Kabupaten / Kota di Provinsi Sumatera Utara - Murni Dahlena; Junita Putri Rajana Harahap (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
A APBD shows the potential ability of a region to manage its regional resources to be a source of income in the context of regional development and prosperity. This research was conducted to analyze and identify the financial capacity of the region for the purposes of planning the following year or other interests. Regional Revenue and Expenditure Budget (APBD) is a financial plan prepared by each region based on Regional Regulations, in this case the regency / city area in North Sumater Province. This study uses district / city APBD data in North Sumatra Province for the past 4 years, from 2014 to 2017. The results of this study indicate that the financial performance of district / city governments in North Sumatra Province is good and independent, marked by the large components Regional original income continues to increase from 2014 to 2017. Keywords : Revenue, Expenditure, Performance